The man in the window - Cohen, Jon (Book lust rediscoveries., 2013)
Since he was disfigured in a fire sixteen years ago, recluse Louis Malone has remained hidden from the prying eyes of his neighbors in the small town of Waverly. Across town, Iris Shula, a lonely and unlovely nurse, knows at thirty-seven it is unlikely that her Prince Charming will ever appear. But Iris is about to learn how wrong she is. When Louis accidentally falls out of his second-story window, these two kindred souls are brought together. What unfolds is a most unlikely love story. One that will make you laugh and that will break--and remake--your heart.